Forever never - Score, Lucy (Las Vegas, NV : That's What She Said Publishing, Inc., 2021)
You don$1 (Bt fall for your brother$1 (Bs high school sweetheart, your boss$1 (Bs daughter, or your ex-wife$1 (Bs best friend. Especially when they$1 (Bre all the same woman. Under Brick Callan$1 (Bs mile-wide chest beats a loyal heart with a few cracks in it. He$1 (Bs the steadfast, overprotective type. Especially when it comes to the one woman he can never have. It$1 (Bs a long, complicated history punctuated by fights, friendship, family, and an attraction that strains his iron willpower. When Remi Ford returns to Mackinac Island in the dead of winter with a secret, Brick makes it his mission to find out what put the shadows in those green eyes. Even if it means breaking down the walls he$1 (Bs built between them. Even if it means falling for the one girl he$1 (Bll never get over. The free-spirited artist just needs to lay low for a few weeks so she can figure a way out of this nightmare. She$1 (Bs definitely not staying. Not when the man who broke her teenage heart into splinters keeps showing up at her parents$1 (Bdinner table. Remi doesn$1 (Bt need broody, bearded Brick riding to her rescue$1! =(Bagain. Not when it will put them both in danger, costing them much more than their hearts.s
Keywords: Man-woman relationships -- Fiction; Artists -- Fiction; Romance fiction